Upregulation of Versican Associated with Tumor Progression, Metastasis, and Poor Prognosis in Bladder Carcinoma - Zhang, Qi (Biomed Res Int, 2021)
OBJECTIVE: This work analyzes the role of versican (VCAN) on bladder cancer (BLCA). Versican (VCAN) is a chondroitin sulfate proteoglycan which is important for tumorigenesis and the development of cancer. However, the expression of VCAN on human bladder cancer (BLCA) has been rarely reported. METHODS: The clinical significance of VCAN in BLCA has been determined by our bioinformatics tools. Then, we performed immunohistochemical staining (IHC) and analyzed the correlation between VCAN expression and clinicopathological features. RESULTS: The bioinformatics results reveal that a high VCAN mRNA level was significantly associated with stage, histological subtype, molecular subtype, and metastasis in BLCA. Furthermore, IHC reveals that expression of VCAN was significantly correlated with the number of tumors, invasion depth, lymph node metastasis, distant metastasis, and histological grade. Kaplan-Meier survival analysis reveals that patients with a high expression of VCAN have poor prognosis than those patients with a low expression of VCAN. According to our result from the bioinformatics database, the mechanism of VCAN in BLCA revealed that VCAN was related to FBN1 and genes of the ECM remodeling pathway (MMP1, MMP2). CONCLUSION: VCAN expression might be included in the process of carcinogenesis and prognosis. Hence, VCAN could be a reliable biomarker of the clinical prognosis on BLCA.